UPAYA GREEPEACE DALAM MENANGANI KERUSAKAN LINGKUNGAN PASCA KEBAKARAN HUTAN DAN LAHAN DI INDONESIA - Bella Putri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to determine about Greenpeace’ effort to handle of Environmental Damage After Forest and Land Fires in Indonesia.  During 2015, Indonesia experiences El Nino season that causes dryness. It is created  hotspots around the forest and land flammable. It’s getting worse because there were large opening of oil palm plantations in peatland and forest areas by cutting-burning to save the costs. Land clearing also experienced problem within the management due to overlapping permissions issued by the government. This incident led Greenpeace as an NGO to save the environment and take part in deal with environmental demage following forest and land fires with several forest-related programs.  This research uses the Perspective of Contructivism, Group Organization the level analysis, Theory of International Organizations  and the concept of Environmental Security. This research data is obtained from books, journals, offical documents and website that support the hypothesis. The research method used is descriptive with literature studies.The result of this research is the efforrt that conducted by Greenpeace to handle environmental demage after forest and land fires in Indonesia“Forest Without Fire Campaign”; launched a program named Interactive Map Kepo Hutan, Tiger Challenge, Create Fire Prevention Team, launched toolkit of High Stock Carbon (HSC) Approach, and the partnership Greenpeace with government. Keyword : Greenpeace Effort, Forest and Land Fires, Environmental damage.     International Organizations.